A dynamic reversible RNA N6‐methyladenosine modification: current status and perspectives. Issue 6 (15th January 2019) - Bi, Zhen; Liu, Youhua; Zhao, Yuanling; Yao, Yongxi; Wu, Ruifan; Liu, Qing; Wang, Yizhen; Wang, Xinxia
Abstract: N 6 ‐methyladenosine (m 6 A), as the most abundant RNA epigenetic modifications, has been shown to play critical roles in various biological functions. Research about enzymes that can catalyze and remove m 6 A have revealed its comprehensive roles in messenger RNA (mRNA) metabolism and other physiological processes. The "readers" including YTH domain‐containing proteins, hnRNPC, hnRNPG, hnRNPA2B1, IGF2BP1, IGF2BP2, and IGF2BP3, which can affect the fates of mRNA in an m 6 A‐dependent manner. In this review, we focus on recent advances in the research of the m 6 A modifications, especially about the latest functions of its writers, erasers, readers in RNA metabolism, cancer, and lipid metabolism. In the end, we provide insights into the underlying molecular mechanisms of m 6 A modifications. Abstract : In this review, we focus on recent advances in the research of the m6A modifications, especially about the latest functions of its writers, erasers, readers in RNA metabolism, cancer, and lipid metabolism. In the end, we provide insights into the underlying molecular mechanisms of m6A modifications.